Cryptocurrencies: Miner Heterogeneity, Botnets, and Proof-of-Work Efficiency - Schär, Fabian (Frontiers in Blockchain, 2020)
Proof-of-work cryptocurrencies are heavily criticized for the alleged inefficiency of their mining mechanism. However, critics fail to distinguish between the resources that are used to secure the blockchain and those that are wasted. In this paper, we introduce a simple mining model and use this model to analyze the consensus protocol's efficiency, while accounting for the heterogeneity of the miners involved. We categorize the resources allocated by the miners as either useful or wasteful, and then use this to introduce a new measure of efficiency. We then demonstrate how this value depends on a set of potential miners and the variation of their marginal costs. Using this model, we then consider the existence of botnets and show how one could affect the security of the network. This analysis indicates that botnets can significantly change the mining landscape and, under certain circumstances, may lead to a dissipation ratio greater than one.